Asia's latent nuclear powers Japan, South Korea and Taiwan - Fitzpatrick, Mark (Adelphi (Series) (International Institute for Strategic Studies), 2016)
Under what conditions would the democracies in Northeast Asia seek to join the nuclear weapons club? Japan, South Korea and Taiwan are threshold nuclear powers by virtue of their robust civilian nuclear-energy programmes. All three once pursued nuclear weapons and all face nuclear-armed adversaries. Fitzpatrick's latest book analyses these past nuclear pursuits and current proliferation drivers. It considers how long it would take each to build a nuclear weapon if such a fateful decision were made but does not predict such a scenario. Unlike when each previously went down a nuclear path, democracy and a free press now prevail as barriers to building bombs in the basement. Reliance on US defence commitments is a better security alternative--as long as such guarantees remain credible. But extended deterrence is not a barrier to proliferation of sensitive nuclear technologies. Nuclear hedging by its Northeast Asian partners will challenge Washington's nuclear diplomacy.